Mapping Structural and Linguistic Errors in Junior High School Students' Procedure Text Writing - Engla Sabdatino Rahmadhani; Afnita; Farel Olva Zuve; Mita Domi Fella Henanggil (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2026)
The skill of writing procedural texts that integrate structural completeness and linguistic accuracy remains a challenge for junior high school students post-pandemic. This study aims to describe the structure and linguistic usage in procedural texts written by seventh-grade students at SMP Negeri 7 Kubung. This research is a qualitative study using a descriptive method. The data for this study consist of the structures and linguistic elements found in the students' procedural texts. The results show that, in general, students' manuscripts already include the five structures of procedural texts: title, objectives, tools and materials, steps, and conclusion. However, in terms of accuracy, the sections least often written correctly by students are the objectives and conclusion sections. Second, in terms of language, including punctuation, capital letters, and standard and non-standard words, students have used them quite well. These findings imply the need for educators to focus not only on operational instructions for texts but also on improving writing habits in the narrative-persuasive section and on the accuracy of students' self-editing.